2010
DOI: 10.1159/000284360
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinemia: Different Clinical Expression in Childhood

Abstract: Background: Hyperprolactinemia is the most common disturbance in pituitary gland secretion. Functional diversity of prolactin action is responsible for different initial clinical expressions of hyperprolactinemia. Patients and Methods: We investigated causes of hyperprolactinemia in 11 children and adolescents (6 females and 5 males), aged from 1.5 to 17.5 years. Children with primary hypothyroidism, iatrogenic hyperprolactinemia and adolescents with polycystic ovaries were excluded. Results: Four patients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…He then started GH replacement therapy, which was maintained until the age of 16 years. Growth deficiency has been reported in another study [11] in 24% of all patients with similar characteristics to those of our patient, in 4 patients in a group of 11 children [21], and in only 1 individual among a sample of 26 adolescents [12]; however, other authors found no growth deficiency in a study with 39 children [20]. …”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…He then started GH replacement therapy, which was maintained until the age of 16 years. Growth deficiency has been reported in another study [11] in 24% of all patients with similar characteristics to those of our patient, in 4 patients in a group of 11 children [21], and in only 1 individual among a sample of 26 adolescents [12]; however, other authors found no growth deficiency in a study with 39 children [20]. …”
Section: Discussionsupporting
confidence: 86%
“…Other authors have also shown this effect in patients younger than 20 years [11-14, 20, 21]. However, despite the use of bromocriptine for 34 months and cabergoline for 252 months at high doses (4.5 mg per week), the tumor in our patient did not disappear, but rather it became cystic.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…Although more common in adulthood compared to childhood, suspected hyperprolactinemia is the main indication for prolactin measurement. In most cases, pituitary adenomas are responsible for the increased secretion of this hormone and, therefore, serum prolactin measurement should be included in all cases of suspected pituitary disease (21,22 ). The finding in the present study that sex partitioning is not required for prolactin reference intervals is in agreement with others (4,23 ).…”
Section: Discussionmentioning
confidence: 99%